Early multidrug treatment of SARS-CoV-2 infection (COVID-19) and reduced mortality among nursing home (or outpatient/ambulatory) residents. (August 2021) - Alexander, Paul E.; Armstrong, Robin; Fareed, George; Lotus, John; Oskoui, Ramin; Prodromos, Chad; Risch, Harvey A.; Tenenbaum, Howard C.; Wax, Craig M.; Dara, Parvez; McCullough, Peter A.; Gill, Kulvinder K.
Abstract: The outbreak of COVID-19 from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread all over the world with tremendous morbidity and mortality in the elderly. In-hospital treatment addresses the multifaceted nature of the illness including initial viral replication, cytokine storm, and endothelial injury with thrombosis. We identified nine reports of early treatment outcomes in COVID-19 nursing home patients. Multi-drug therapy including hydroxychloroquine with one or more anti-infectives, corticosteroids, and antithrombotic anti-blood clotting agents can be extended to seniors in the nursing home setting without hospitalization. Data from nine studies found hydroxychloroquine-based multidrug regimens were associated with a statistically significant > 60% reduction in mortality. Going forward, we conclude that early empiric treatment for the elderly with COVID-19 in the nursing home setting (or similar congregated settings with elderly residents/patients e.g. LTF or ALF) has a reasonable probability of success and acceptable safety. This group remains our highest at-risk group and warrants acute treatment focus prior to symptoms worsening. Given the rapidity and severity of SARS-CoV-2 outbreaks in nursing homes, in-center treatment of acute COVID-19 patients is a reasonable strategy to reduce the risks of hospitalization and death. If elderly high-risk patients in such congregated nursing home type settings are allowed to worsen with no early treatment, they may be too sick and fragile to benefit from in-hospital therapeutics and are at risk for pulmonary failure, life-ending micro-thrombi of the lungs, kidneys etc. The issue is timing of therapeutics, and we argue that early treatment before hospitalization, is the right time and can potentially save lives, especially among our higher-risk elderly populations hit hardest by severe illness and death from COVID-19. We must reiterate, we are talking about 'early' treatment before the disease is far along in the disease sequelae where the patient then needs hospitalization and aggressive interventions. We are referring to the initial days e.g. day one, post infection when symptoms emerge or there is strong clinical suspicion. This early therapeutic option deserves serious and urgent consideration by the medical establishment and respective decision-makers. Doctors must be allowed their clinical discretion in how they optimally treat their patients. Doctors must be brave and trust their skilled judgements and do all to save the lives of their patients. We therefore hypothesize that early outpatient ambulatory treatment, once initiated as soon as symptoms begin in high-risk positive persons, would significantly reduce hospitalizations and prevent deaths. Specifically, the provision of early multi-drug sequenced therapy with repurposed drugs will reduce hospitalization and death in elderly patients being cared for in long-term-care facilities. The most important implications of our hypothesis are: 1) hospitalizations and deaths would be reduced 2) transmission would be reduced due to the mitigation of symptoms and 3) recovery following infection and treatment provides for natural exposure immunity that is broad based, durable, and robust (helping towards natural immunity within the population). The end result is reduced strain on hospitals and systems that would allow for other non-COVID illnesses to receive care.